ANALISIS KEPERCAYAAN DIRI ANAK DALAM KESENIAN TARI TRADISIONAL DI PAUD KASIH IBU - Siti Aminah; Maulida Nur; Havid Surya (STKIP Subang, 2026)
This study aims to analyze the implementation of traditional dance activities in fostering self-confidence among early childhood learners at PAUD Kasih Ibu, Sukawana Village, Curug District, Serang City, as well as to identify the influencing factors. Self-confidence is considered a crucial aspect of social-emotional development that must be nurtured from an early age. Traditional dance was selected as a learning medium because it accommodates self-expression, builds courage to perform in public, and strengthens peer interaction. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving four children aged 5–6 years as primary subjects and three teachers as supporting informants. The implementation of dance activities included routine practice, introduction of basic movements, use of simple costumes, and stage performances during school events. The findings indicate that children demonstrated improved self-confidence, reflected in their willingness to perform, expressive movement skills, and active participation with peers. Factors influencing self-confidence included parental support, responsive teaching strategies, and a supportive learning environment. Therefore, traditional dance can be positioned as an effective pedagogical strategy to stimulate and strengthen self-confidence in early childhood.